Pharmacogenomics of CYP2D6 - Chamboko, Chiratidzo Respina (Rhodes University, 2026)
Over the past few years, pharmacogenomics research has gained more attention due to the growing interest in personalized medicine. Polymorphisms in pharmacogenes have greatly affected drug therapies and this either causes low drug efficacy or adverse drug reactions in humans. Specifically, polymorphisms in pharmacogenes that encode drug metabolizing enzymes from the first three families of human cytochrome P450 (CYP) enzyme enzymes have been major contributors, as these enzymes metabolize numerous xenobiotics and drugs on the market today. Cytochrome P450 2D6 (CYP2D6), a CYP2 family enzyme, accounts for at least 25% of drug metabolism, making it one of the key enzymes for pharmacogenomic research. Studies on this enzyme will essentially lead to personalized medical therapies for a wide range of drugs. In the research conducted here, investigations were conducted to advance 3D pharmacogenomic research on CYP2D6, with an emphasis on African populations, which have been underrepresented in this field. The first aim of this study was to characterize enzymes within CYP families 1, 2 and 3, so as to uncover structural and sequential characteristics that may be shared among all enzymes within the three families, and identify those that may be unique to each family, and particularly, unique to CYP2D6. In silico processes such as multiple sequence alignment, motif analysis and phylogenetic tree construction were employed to analyze sequences from the three families. Through analysis, it was observed that the three enzyme families contain defined conservation in regions close to or in contact with the heme group, however unique patterns were detected within each CYP enzyme family, and these regions were located towards the helices responsible for substrate specificity and active site access. This indicated relationships within families were stronger, and phylogenetic analysis highlighted this with family-wise clustering of sequences observed. With the results obtained from this research, it is evident that similarities within the three families do exist, but each family contains unique sequence and structural features that possibly relate to the different drugs they metabolize. Interestingly, CYP2D6 was noted to have fewer unique regions in comparison to other enzymes within the CYP2 family, which may explain its ability to metabolize a wider variety of drugs than other enzymes. The next aim was to generate a potentially more effective way of assessing CYP2D6 reduced function, by investigating the possible variant-induced mechanisms leading to the reduced activity of CYP2D6, then thereafter apply these mechanisms to Afrocentric alleles with unknown function at the time of this research, to observe if any likely harbored this activity. Several computational techniques and tools were utilized to achieve this aim. The analysis was conducted with CYP2D6 alleles *2, *10, *14, *17, *27, *29, *33, *34, *39, *45, *48, *49, *50, *53, *54, and *55 with known normal or reduced function, and Afrocentric alleles *149, *152, *153, *154, *155, *157, *159, *160, *162 and *163 with unknown clinical activity. Molecular dynamics (MD) simulations and traditional post-MD analyses, including RMSD and Rg, were used to assess structural stability changes in CYP2D6 alleles. Geometric clustering was applied to evaluate allele conformations after stabilization and secondary structure alterations were analyzed with the DSSP tool and ΔRMSF. Hydrogen bonding throughout the different systems was also conducted to observe changes in hydrogen bonding due to variation presence. We examined heme interactions by measuring the center of mass between the heme and the active site, hydrogen bonding, and contacts with surrounding residues, then tunnel analysis of whole protein systems was conducted to observe dominant tunnel opening frequencies. Finally, DRN metrics were employed to detect variation-induced changes in allele communication. The key findings within this study prompted the proposal of four mechanism that potentially lead to reduced activity within CYP2D6 alleles, which are: 1) instability and conformational changes of protein; 2) secondary structure variation and changes in flexibility of ≥3 highly important protein regions; 3) more frequently closed/ more than one frequently open or partially open channel simultaneously; 4) unique changes in inter-residue communications within the B’ helix and/or β1 sheet region. We also proposed from data analyzed, that when predicting reduced functionality on alleles with unknown activity, the allele must have at least three of the mechanisms occurring. This then led to the potential prediction of reduced activity among some of the Afrocentric alleles studied here. Overall, this study contributes to the pharmacogenomic research on CYP2D6 enzymes. It unveiled the effects of variations in CYP2D6 alleles and identified potential mechanisms that may bring about reduced activity of these alleles. This study also contributed to the knowledge of functionality of novel Afrocentric alleles with no clinical activity as yet, that could potentially be useful in personalized medicine.
a study of CYP2D6 and its allelic variants using in silico approaches
Keywords: Pharmacogenomics; Precision medicine; Cytochrome P-450 CYP2D6; Single nucleotide polymorphisms; Allele